Analisis Pengaruh Celebrity Endorsement Dan Brand Image Terhadap Minat Beli Pada Pengguna Aplikasi DANA - Fawwaz Al Aziz (2021)
DANA Dompet Digital is an e-wallet company originating from Indonesia and developed by a startup company that already has an Indonesian legal entity carried out by young Indonesian programmers. DANA's role as a new competitor in digital-based wallet applications in Indonesia immediately showed its courage to be a pioneer of digital-based wallet applications in Indonesia. The purpose of the study was to find out the effect of Celebrity Endorsement and Brand Image on buying interest in Dana Application users. The population in this study were UPN Veterans Jakarta students majoring in Management S1 Class of 2017. This study used a total sample of 50 people by calculating the use of the Roscoe formula. The data obtained in this study are primary data, namely through the distribution of questionnaires or questionnaires through the g-form. The data analysis technique that will be carried out in this research is quantitative data analysis technique using statistical methods. The statistical method used is Partial Least Square (PLS). The test results show that (1) Celebrity Endorsements have a positive and significant effect on buying interest of UPN Veteran Jakarta students/I and (2) Brand Image has a positive and significant impact on buying interest of UPN Veteran Jakarta students.